2020
DOI: 10.3390/ijerph17207447
|View full text |Cite
|
Sign up to set email alerts
|

German Dentists’ Preferences for the Treatment of Apical Periodontitis: A Cross-Sectional Survey

Abstract: Currently, there is no standard treatment protocol for apical periodontitis (AP). Thus, restorable teeth might get extracted and replaced prosthetically. This study evaluated German dentists’ preferred AP treatment decisions and the influencing factors for selecting tooth retention by initial/repeated surgical/non-surgical root-canal treatment (RCT) or extraction with/without prosthetic replacement. Through an online-survey, participants (n = 260) rated different treatment options for four case scenarios with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
(81 reference statements)
1
12
0
1
Order By: Relevance
“…In this survey 732 dentists participated via the online survey link and completed the online questionnaire, displaying a significant sample size and representing German dentists in the investigation. Sociodemographic data of the participants presented an analogous gender distribution compared to the dental population in Germany (60–70% female) and Europe ( Table 1 ) with higher percentages of female dentists [ 23 , 38 ]. The majority of the survey participants were younger than 50 years old and working in dental practices ( Table 1 ).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In this survey 732 dentists participated via the online survey link and completed the online questionnaire, displaying a significant sample size and representing German dentists in the investigation. Sociodemographic data of the participants presented an analogous gender distribution compared to the dental population in Germany (60–70% female) and Europe ( Table 1 ) with higher percentages of female dentists [ 23 , 38 ]. The majority of the survey participants were younger than 50 years old and working in dental practices ( Table 1 ).…”
Section: Discussionmentioning
confidence: 89%
“…First of all, the investigation is restricted by its cross-sectional nature and lacks the follow-up on a longitudinal level. On the other hand, misinterpretations in such investigations are known to be equally dispersed [ 23 ]. In this survey, the observed outcomes of German dentists cannot be accredited exclusively to the analyzed aspects and socio-environmental information.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This exercise could be done with older students and compared to dentists to show a different effect. The degree of difficulty for an optimal operation is increased in this case, because for a decent apicoectomy, as little bone and dentine or tooth structure as possible, but as much gutta-percha from the orthograde filling and infected tissue as necessary, should be removed [ 37 ], which influences the outcome in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…One of the disadvantages of cross-sectional studies is the limited evaluation of data aside from the information gathered. However, similar studies have shown that this limitation of cross-sectional surveys has a weak effect on evaluation, as misdiagnoses of gathered data tend to be equally distributed [ 65 ]. In this survey, the detected oral health behaviour and attitudes of preclinical and clinical dental students at Ain Shams University cannot be completely ascribed to the examined aspects and the sociodemographic data.…”
Section: Limitations Of the Studymentioning
confidence: 99%